Development of a novel bioreactor and systems for suspension cell culture in biopharmaceutical production - Sharma, Rajesh (Department of Chemical Engineering, 2022)
Mammalian cells offer superior cellular machinery for the production of complex biological products. These cells provide proper post-translational processing machinery for recombinant protein expression to acquire the desired folding for optimal activity. With this advantage, mammalian cells have become the preferred choice for the production of biological products. These cells may grow either attached to a solid surface (adherent cells) or, where adapted, as suspension cultures. In order to grow these cells efficiently in suspension, a bioreactor is therefore required. Bioreactors play a key role in the production of biologicals. Due to the continuous advancement of medicine and the healthcare industry, the demand for biological drugs has increased in the last three decades. This has placed a significant pressure on the biopharmaceutical industry to meet this increasing demand and has become a key driving force behind the need to develop better, safer and more economical bioreactor designs and culture processes. Continuous stirred tank bioreactor is the norm for production of many bioproducts. However, these bioreactors exert high shear forces to cells due to the impeller speed, bubble disruption, and foam formation. In addition, at a large scale, improper mass transfer impairs the performance of cell lines and achieving high cell densities and prolonged viability with correct glycosylation of a secreted proteins is still a challenge during scale-up. Many cell lines, for example Vero cells, which are widely used to produce human vaccines are difficult to adapt into suspension culture. Fixed-bed bioreactors and the use of microcarriers provide an alternative platform for their growth to produce biologicals. However, a high surface area is required to achieve the high cell density which leading to an elevated cost of production (mainly from microcarriers) and ensuing a costly and technically challenging scaling-up of these systems. Other designs such as single-use bioreactors and novel bioreactors based on different operating principles have been explored, but their utilisation is limited from laboratory to pilot scale. Hence, a comprehensive bioreactor design which would be suitable for a large variety of cell lines to produce high-yielding products in suspension culture with the lowest cost and risk in the shortest span of time is still sought. In the current research, two approaches were investigated to address these challenges. Firstly, a horizontal tubular bioreactor (HTB) with a spiral impeller was designed and fabricated for the propagation of suspended mammalian cells with a focus to achieve middle to high cell density by improving mass transfer whilst reducing hydrodynamic shear and energy requirements through surface aeration. The second approach is to test the adaptation of adherent Vero cells into single-cell suspension culture in serum-free media by treating them with an anti-cancer drug, Puromycin amino nucleoside (PAN). The absence of a supporting surface for cell growth (e.g. microcarriers) and serum-free conditions are expected to reduce the cost of manufacturing and to achieve higher productivity of biological production per unit volume of bioreactor. In the first approach, the horizontal tubular vessel was designed to achieve the final volume of approximately 5.0 L. Design of the impeller is a key component that dictates the mixing patterns and mass transfer efficiency. Different geometric configurations were used to design the spiral impeller by considering various parameters such as impeller diameter, the pitch of the blade, pitch angle, height of the blade, the thickness of the blade, clearance efficiency and the position of the heating element. Another important aspect of the prototype design was incorporating an external magnetically-coupled motor drive which assisted in not only in aseptic handling but also reduction in mechanical stress and generation of fewer particles for cleanroom operations. The side plate was designed with the appropriate number of addition ports to allow execution of batches with minimum cross-contamination and for the ease of operation. Thereafter, the engineering characterisation of the HTB was carried out.